The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.2134/jeq2018.11.0397
|View full text |Cite
|
Sign up to set email alerts
|

Adding Phosphate Fertilizer and Apple Waste to Pig Manure during Composting Mitigates Nitrogen Gas Emissions and Improves Compost Quality

Abstract: Calcium superphosphate and apple (Malus pumila Mill.) waste can be used for controlling N loss and improving compost quality during composting, whereas integrated addition of the two additives on composting process remains unexplored. Therefore, this study was conducted to investigate the effects of combined use of calcium superphosphate and apple waste on NH3 and N2O emissions and compost quality during pig manure and wheat (Triticum aestivum L.) straw composting. Mixtures of pig manure and wheat straw were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 42 publications
0
0
1
Order By: Relevance
“…Our results are also consistent with the ndings of Cadot (2018) who reported that fertilization can signi cantly increase the number of results per corn plant and the weight of stems and leaves (Table 2). In the current study, higher plant height and thicker stem diameter were found after the manure fertilizer treatments (MN, MNP), but there was no signi cant difference between the unfertilized and mineral fertilizer (NF, NP) soils, which is inconsistent with previous research suggesting that fertilizer application increases the height and stem of plants (Jiang et al, 2019). The higher nutrient content in soil caused by the application of manure, and a signi cant reduction in the soil pH after application of mineral fertilizer (Table 1; Kmet'ova and Kovacik, 2013).…”
Section: Discussioncontrasting
confidence: 99%
“…Our results are also consistent with the ndings of Cadot (2018) who reported that fertilization can signi cantly increase the number of results per corn plant and the weight of stems and leaves (Table 2). In the current study, higher plant height and thicker stem diameter were found after the manure fertilizer treatments (MN, MNP), but there was no signi cant difference between the unfertilized and mineral fertilizer (NF, NP) soils, which is inconsistent with previous research suggesting that fertilizer application increases the height and stem of plants (Jiang et al, 2019). The higher nutrient content in soil caused by the application of manure, and a signi cant reduction in the soil pH after application of mineral fertilizer (Table 1; Kmet'ova and Kovacik, 2013).…”
Section: Discussioncontrasting
confidence: 99%